(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The world is changing daily, and the educational system has grown to meet the needs of society while retaining its philosophical component. In this age of globalization and modernization, paradigm shift has been observed in a number of areas of the education system, including teaching methods, the use of TLM, and teacher training programs. The current teaching-learning approaches are not thought to meet the needs of the younger generation of students. Building a digital village where the next generation acts as a digital nation is crucial for the younger generation of learners. In order to build a new teaching-learning environment, the phrase Techno-Pedagogical Competency has been used in bite-sized learning, cloud learning, steam curriculum, etc. However, the way that students have been using cloud-based applications will be significant since it will help teachers create more effective digital apps for the education sector and better course designs for online learning settings. The purpose of this study is to demonstrate how, in the wake of COVID-19, the use of Techno-Pedagogical Competency through the use of cloud learning, bite-sized learning, and steam curriculum has altered our way of thinking, working, and maintaining our way of life.